Towards a natural classification of Sordariomycetes: The genera Frondisphaeria, Immersisphaeria, Lasiobertia, Pulmosphaeria and Yuea (Sordariomycetes incertae sedis) - Daranagama, Dinushani A.; Liu, Xingzhong; Chamyuang, Sunita; Stadler, Marc; Bahkali, Ali; Hyde, Kevin (Phytotaxa, 2016)
The type specimens of Frondisphaeria, Immersisphaeria and Pulmosphaeria were re-examined in order to determine their familial placements according to modern taxonomic concepts. Type specimens of Lasiobertia and Yuea were redrawn from the original descriptions. Based on morphological evidences, Frondisphaeria palmicola is placed in Diatrypaceae. Immersisphaeria eichleriana, Lasiobertia africana and Pulmosphaeria archontophoenicis are placed in Xylariales incertae sedis as they are not typical of any existing families of Xylariales. A possible relationship with Xylariaceae is suggested for Yuea chusqueicola based on the previously described morphological characters. Recollection of fresh materials, epitypification and multi-gene phylogenetic analyses are essential for all type species of these genera to clarify their familial status.